Gastrointestinal Oncology A Practical Guide - Blanke, Charles D.; Rödel, Claus; Talamonti, Mark S. (Springer Berlin Heidelberg : Imprint: Springer, 2011)
Gastrointestinal Oncology is an evidence-based, practical reference intended to assist in the diagnosis and management of patients with gastrointestinal malignancies. It is designed to be as user friendly as possible and is distinguished by the extremely practical, concrete nature of the information presented and by the multidisciplinary approach adopted. In addition to disease-oriented chapters spanning sites from the esophagus to the anus, non-anatomic subjects such as modern imaging techniques are also addressed. Translational science is supplied where useful in the decision-making process. All of the authors are internationally recognized experts. This book is an ideal resource for oncologists, surgeons, gastroenterologists, and primary-care providers looking for the latest and best information on how to deal with a wide variety of gastrointestinal neoplasms.